Iron ore milling and the comminution process: a bibliometric analysis - Cordeiro, Kamila Antunes; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2021)
The context of the growing global scarcity of high iron content ores is a stimulus for the fragmentation equipment for less concentrated fines to be increasingly used and their studies revisited. This study had as its premise the investigation of scientific production regarding the process of comminution of iron ore through grinding. Methodologically, a bibliometric analysis was carried out through the selection of articles in the collection available free of charge to compose the portfolio, in order to map the pertinent literature, describe which means the most relevant studies on the subject are inserted, and so by individual listings proceed their qualitative analysis. The results address the importance of testing solutions and improving studies in this area, as it has great potential and the need for technical and operational improvements that enable an improvement in the specific cost of the product. Therefore, several authors highlight solutions for a more efficient processing of the fragmentation of this ore in the midst of the current economic challenge.